Is exposure to animal feces harmful to child nutrition and health outcomes? A multicountry observational analysis - Headey, Derek D.; Nguyen, Phuong Hong; Kim, Sunny S.; Rawat, Rahul; Ruel, Marie T.; Menon, Purnima (American Society of Tropical Medicine and Hygiene, 2017)
As of 2011, stunting—height-for-age z scores (HAZ) < −2—affects one in four preschool children.1 Stunting in early life has been linked to poor health and cognition, as well as reduced educational attainment and lower adult earnings.2–5 The reduction of stunting is therefore seen as an increasingly important long-term investment.4,6 Strategies for stunting reduction principally focus on improving infant and young child feeding (IYCF; including dietary diversification), and on preventing infections that reduce appetite, inhibit the absorption of nutrients and divert resources away from growth and development. In the developing world, livestock ownership is regarded as an important means of diversifying diets through its role in income generation, as well as through directly improving household access to nutrient-rich animal-sourced foods.7–10 However, it has also been posited that exposure of children and their caregivers to animal feces is a potential risk factor for infections. A recent systematic review of 27 prior studies linking animal exposure to diarrhea symptoms or pathogens found that 20 studies showed significant positive linkages.11 In most of these studies, only a small proportion set out to specifically test diarrheal associations with animal exposure, only nine reported on their methods of recording animal exposure, and the body of evidence overall was determined to be of low quality. In addition to limited attention from researchers, strategic thinking and programming on diarrheal control has also primarily focused on reducing exposure to human rather than animal excreta,12 since humans are the main repository for several pathogens most strongly associated with diarrheal illnesses in children.13 Compared with diarrheal illnesses, even less attention has been focused on whether exposure to animal feces might affect child anthropometric outcomes such as height for age (stunting) or weight for height (wasting). Although there is a well-recognized bidirectional relationship between undernutrition and diarrheal illnesses, a growing body of research suggests subclinical environmental enteric disorder (EED)—rather than clinical diarrhea—is the primary causal pathway from poor sanitation and hygiene to stunting.14–17 EED is characterized by chronic damage to the small intestine, which inhibits the absorption of nutrients, but also triggers a low-level immune system stimulation (inflammation) that diverts resources away from physical and cognitive development, and leaves children more exposed to infections. Some of this research also hypothesizes that while the more pathogenic bacteria in human excreta may be the more important cause of diarrheal illnesses in young children, animal excreta may be an important reservoir of nonpathogenic bacteria that are still capable of causing the chronic subclinical damage to the gut, which is characterized as EED.15 In this regard, a particular concern is the possibility that young children in the developing world frequently ingest animal feces or fecally contaminated soils. Studies in Peru,18 Zimbabwe,19 and Bangladesh20 observed young children over prolonged periods and found that significant proportions ingested soils or poultry feces directly, whereas 28% of mothers in the Bangladesh study reported at least one incident of geophagy in the past week. All three studies showed that chicken feces and fecally contaminated soils had extremely high concentrations of bacteria, including pathogenic bacteria such as Escherichia coli. In a sample of 216 children under 5 years of age, the Bangladesh study found that the odds of being stunted (HAZ < −2) were double for children with caregiver-reported geophagy. Another study by the Bangladesh research team found that biomarkers of EED for these children were significantly associated with having an animal corralled in the child's sleeping room.21 Collectively, these studies suggest that the combination of free roaming livestock and poor hygiene and care practices may be an important underrecognized risk factor for EED and linear growth retardation. Nevertheless, the evidence to date is limited to the aforementioned study in Bangladesh,20 and experimental evidence on these linkages is unlikely to emerge for several more years.22,23 In this study, we therefore use data from large-scale nutrition surveys conducted in Ethiopia, Bangladesh, and Vietnam to address three research questions. First, within these quite different socioeconomic contexts, how prevalent are observable animal feces in household compounds? Second, what factors are most strongly associated with observable animal feces? Third, is the presence of animal feces significantly associated with child height for age (our primary outcome of interest), child weight for height, and child morbidity symptoms?